PENERAPAN MEDIA INTERAKTIF BERBASIS CANVA UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA(STUDI KASUS: STIT SYEKH MUHAMMAD NAFIS TABALONG) - Hatmiah Hatmiah (ADIBA : JOURNAL OF EDUCATION, 2025)
This study aims to determine the application of interactive media based on Canva to improve student learning outcomes at STIT Syekh Muhammad Nafis Tabalong. The formulation of the problem in this study is how to apply interactive media based on Canva to improve student learning outcomes at STIT Syekh Muhammad Nafis Tabalong. This type of research is field research and the approach used is a qualitative approach. The subjects of this study were lecturers and students at STIT Syekh Muhammad Nafis Tabalong. The object of this study is the application of interactive media based on Canva to improve student learning outcomes at STIT Syekh Muhammad Nafis Tabalong. The data collection techniques were carried out by interview, observation and documentary. Data processing techniques used data reduction, data display and data verification and data analysis using qualitative descriptive. The results of the study showed that the application of interactive media based on Canva to improve student learning outcomes at STIT Syekh Muhammad Nafis Tabalong was successful, because the average student score increased significantly after using Canva. In addition, students become more active and involved in learning, with the visualization and interactivity offered by Canva increasing their understanding of the material. Further discussion shows that Canva is effective in supporting diverse learning styles, improving critical thinking skills, and facilitating collaborative learning. The conclusion of this study is that Canva-based interactive media can significantly improve student learning outcomes and support a more effective and interactive learning process. However, the success of implementing this media is highly dependent on teacher competence and adequate technological infrastructure support. This study recommends improving teacher training and infrastructure development to optimize the use of Canva in education.